Factors Affecting Community Treatment in Bandar Masilam Health Center, Bandar Masilam District, Simalungun Regency - Mustaruddin (PT Inovasi Pratama Internasional, 2023)
Community behavior in seeking treatment varies, influenced by several factors, namely: motivation, knowledge, distance to the health center, health workers, treatment costs, and health facilities. This study aims to identify the factors that influence people to go to the Health Center for treatment by using an exploratory descriptive design. The number of samples in this study were 100 respondents who were visitors to the Bandar Masilam Public Health Center, Bandar Masilam District, Simalungun Regency. Sampling using convenience sampling technique in accordance with the research criteria. Data collection was carried out from April 14 to May 30 2014 using a demographic data questionnaire and a questionnaire on factors influencing people to seek treatment at the Health Center, totaling 30 (thirty) statements. The majority of the factors that influenced people to seek treatment at the Health Center were health workers (94%), motivation (90%), medical expenses (80%), health facilities (82%), while the factors that generally had no effect were knowledge (84). %) and the distance to the health center (80%). For this reason, the Health Center needs to carry out socialization efforts that are more related to the various programs and services that have been held at the Health Center. Researchers recommend conducting further research using a larger sample size so that the research results are more accurate.